Comparison of experimental and CFD mass transfer coefficient of three commercial turbulence promoters. (1st March 2016) - Lira-Teco, J.E.; Rivera, F.; Farías-Moguel, O.; Torres-González, J.; Reyes, Y.; Antaño-López, R.; Orozco, G.; Castañeda-Zaldivar, F.
Abstract : Graphical abstract: Highlights: Close agreement between experimental data and CFD calculations. RANS standard κ-ε model was used. High importance of TP orientation was highlighted by CFD calculations. Abstract: The efficiency and performance of electrodialytic cells is based on the flow pattern and mass transfer characteristics, hence, evaluation of cell design, spacers and turbulence promoters (TP), is needed in order to obtain optimal operation. In this, work we compare the mass transfer performance of several plastic nets and cell orientation by means of experimental test and CFD simulation. Excellent agreement in terms of mass transfer was obtained between the two methods. From CFD analysis, it is possible to conclude that the electrochemical reactor design presented in this work, favors the formation of jet flow and stagnant zones in all reactor configurations affecting mass transport flux distribution; this behavior is associated with inlet design and TP orientation. Velocity fields and mass transport flux distributions visualized by CFD analysis, affect the mass transport coefficients values and of course the exact form of dimensionless mass transport correlations here obtained. Finally, 0273R oriented TP configuration seems to have the highest mass transport coefficients, attributed to high contribution of limiting current densities at jet flow zones. A low efficiency under operational conditions is expected.